Cardiovascular toxicity risk assessment of tyrosine kinase inhibitors: a pharmacovigilance study using the VigiBase database - Igawa, Yusuke; Hamano, Hirofumi; Esumi, Satoru; Takeda, Tatsuaki; Kajizono, Makoto; Kikuoka, Ryo; Kimura, Ikuya; Zamami, Yoshito (Frontiers in Pharmacology, 2024)
Introduction: Advances in the early detection and treatment of cancer have significantly improved the prognosis of patients with cancer. Tyrosine kinase inhibitors (TKIs) are effective targeted treatments for various malignancies that act by inhibiting kinase activity. Although these drugs share a common mechanism of action, they differ in their targeted kinases, pharmacokinetics, and side effects. TKIs can cause cardiovascular side effects, which adversely affect the prognosis of cancer survivors. This study aimed to assess the risk of cardiac toxicity associated with TKIs using the World Health Organization Global Database, VigiBase.Methods: We conducted a cross-sectional analysis of data from VigiBase, a comprehensive global database of suspected drug reactions. The dataset included reports up to December 2022. We identified patients treated with Food and Drug Administration-approved TKIs and analyzed their age and sex data. The primary outcome was cardiovascular impairment, defined by 21 preferred terms in the Medical Dictionary for Regulatory Activities Terminology version 25.1. Disproportionality analysis using the reported odds ratio was performed to detect adverse cardiovascular signals. Statistical analyses were conducted using R 3.3.2, with a P-value <.05 considered significant.Results: Of the 32,520,983 reports in VigiBase, 23,181,539 were eligible for the analysis. Significant cardiovascular signals were identified for 17 TKIs, including erlotinib, gefitinib, and imatinib. Stratified analyses revealed potential sex-and age-related differences in the risk of adverse events. Heatmaps indicated significant signals for drugs such as lapatinib in males and gefitinib in younger patients.Discussion: Our findings indicate that some TKIs, particularly those classified as VEGFR, BCR-ABL, and BTK, pose similar risks of cardiotoxicity, while others, including EGFR, HER2, and ALK TKIs, exhibit varied risk profiles. These results underscore the importance of individualized risk assessment and management of TKI-treated patients. In conclusion, this study provides valuable insights into the cardiotoxic risk of TKIs, which is essential for developing tailored treatment plans.